2017
DOI: 10.1177/1073191117740204
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Frost Multidimensional Perfectionism Scale in Spanish Children and Adolescents

Abstract: The Frost Multidimensional Perfectionism Scale (FMPS) is one of the most used instruments to assess perfectionism. The FMPS assesses six dimensions: Concern over Mistakes (CM), Parental Expectations (EP), Parental Criticism (PC), Doubts about Actions (DA), Organization (OR), and Personal Standards (PS). CM, PE, PC, and DA are facets of a more general dimension considered Maladaptive Perfectionism. PS is frequently considered Adaptive Perfectionism. FMPS psychometric properties have been studied in adults but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 107 publications
(247 reference statements)
1
6
0
1
Order By: Relevance
“…While some studies have found no gender difference in perfectionism in college students (Leone & Wade, 2018; Reuther et al, 2013), the inconsistent results might be attributed to different sample sizes, and they have not calculated the effect sizes which might be more accurate to reflect the gender differences in perfectionism. Actually, our results were similar to Gavino’s finding in adolescents (Gavino et al, 2019), in which boys and girls scored differently on several FMPS subscales, but the effect sizes were low.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While some studies have found no gender difference in perfectionism in college students (Leone & Wade, 2018; Reuther et al, 2013), the inconsistent results might be attributed to different sample sizes, and they have not calculated the effect sizes which might be more accurate to reflect the gender differences in perfectionism. Actually, our results were similar to Gavino’s finding in adolescents (Gavino et al, 2019), in which boys and girls scored differently on several FMPS subscales, but the effect sizes were low.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the gender differences in perfectionism, previous studies have yielded inconsistent results. Using FMPS, some studies have shown significant gender differences in perfectionism (Gavino et al, 2019; Morris & Lomax, 2014), where boys scored higher on FMPS total score than girls, while other studies have found no significant gender differences on FMPS total score (Leone & Wade, 2018; Reuther et al, 2013). Andersson et al (2005) found that women scored higher on several dimensions of FMPS (CM, PC and PE) than men, while other studies found no significant gender differences on dimensions of FMPS (Botha & Panebianco, 2018; Sotardi & Dubien, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For Black samples, scholars have reported a Cronbach’s alpha of .88 for the Concern Over Mistakes subscale scores (Castro & Rice, 2003), which is consistent with the current study (sample α = .90). The multidimensional factor structure of the FMPS has been successfully replicated with diverse samples (e.g., Latinx; Gavino et al, 2019). The Concern Over Mistakes subscale has been found to positively correlate (e.g., r = .55) with other indicators of maladaptive perfectionism such as Discrepancy scores on the Almost Perfect Scale-Revised (Slaney et al, 2001), providing evidence for convergent validity (e.g., Sironic & Reeve, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, guided by Hollender's (1965) observation that perfectionists are "fussy, " Frost et al (1990) proposed a sixth dimension, termed organization, that involves an overemphasis on order, precision, and neatness. 2 Numerous studies support the reliability and validity of this widely utilized model (e.g., Gavino et al, 2019;Parker & Adkins, 1995). However, these studies suggest qualifications to Frost et al's (1990) model: Namely, parental expectations and parental criticism are developmental precursors of perfectionism as opposed to core features of perfectionism (Damian et al, 2013).…”
Section: What Is Perfectionism From a Multidimensional Perspective?mentioning
confidence: 99%